Peace Process : American Diplomacy and the Arab-Israeli Conflict since 1967 - Quandt, William B. (Book collections on Project MUSE., 2005)
In this timely new edition of Peace Process, William B. Quandt analyzes how each U.S. president since Lyndon Johnson has dealt with the complex challenge of brokering peace in the Middle East, from the 1967 Arab-Israeli war to the death of Yasir Arafat. This classic work has now been updated to reflect recently declassified U.S. government documents and other published materials relating to the Johnson, Nixon, and Clinton presidencies, and to carry the story through George W. Bush's first term. The most comprehensive account of the Middle East peace process in print, the book.